Vivienne Westwood : the complete collections - Fury, Alexander (Catwalk, 2021)
The only reason I'm in fashion is to destroy the word 'conformity', Vivienne Westwood (b. 1941) declared early in her career. With her provocative synthesis of historic British fashion, classic painting aesthetics, and punk culture, the British designer has continuously revolutionized the fashion industry since her first catwalk collection, "Pirate," debuted in 1981. Opening with a concise history of the house and brief biographical profiles of Westwood and her longtime collaborator Andreas Kronthaler, this spectacular volume--the seventh in the celebrated Catwalk series--documents all of Westwood's catwalk collections from 1981 to today. Short texts illuminating each collection's highlights and influences are accompanied by carefully curated catwalk photographs showcasing hundreds of clothing ensembles, accessories, beauty looks, and set designs, along with the top fashion models who walked the runway, including Kate Moss and Naomi Campbell. With an extensive reference section, this lavishly illustrated volume provides unrivalled insight into one of the most thought-provoking and influential fashion designers in the world.